Effects of submaximal performances on critical speed and power: Uses of an arbitrary-unit method with different protocols - Vandewalle, H. (Sports, 2019)
The effects of submaximal performances on critical speed (SCrit) and critical power (PCrit) were studied in 3 protocols: a constant-speed protocol (protocol 1), a constant-time protocol (protocol 2) and a constant-distance protocol (protocol 3). The effects of submaximal performances on SCrit and PCrit were studied with the results of two theoretical maximal exercises multiplied by coefficients lower or equal to 1 (from 0.8 to 1 for protocol 1; from 0.95 to 1 for protocols 2 and 3): coefficient C1 for the shortest exercises and C2 for the longest exercises. Arbitrary units were used for exhaustion times (tlim), speeds (or power-output in cycling) and distances (or work in cycling). The submaximal-performance effects on SCrit and PCrit were computed from two ranges of tlim (1-4 and 1-7). These effects have been compared for a low-endurance athlete (exponent = 0.8 in the power-law model of Kennelly) and a high-endurance athlete (exponent = 0.95). Unexpectedly, the effects of submaximal performances on SCrit and PCrit are lower in protocol 1. For the 3 protocols, the effects of submaximal performances on SCrit, and PCrit, are low in many cases and are lower when the range of tlim is longer. The results of the present theoretical study confirm the possibility of the computation of SCrit and PCrit from several submaximal exercises performed in the same session.